Circulating T-regulatory cells, exercise and the elite adolescent swimmer - Wilson, L. D.; Zaldivar, F. P.; Schwindt, C. D.; Wang-Rodriguez, J.; Cooper, D. M. (Pediatric Exercise Science, 2009)
Brief high intensity exercise induces peripheral leukocytosis possibly leading to a higher incidence of allergic symptoms in athletes undergoing excessive training. We studied the exercise-induced alternation of circulating Tregs and FoxP3+ Tregs due to acute intense swim exercise in elite swimmers (n = 22, 12 males, age = 15.4 yrs). Twelve had prior or current rhinitis or asthma and 10 had no current or prior allergy or asthma. Circulating Tregs increased significantly (p < .001) following exercise (pre = 133 ± 11.2, post = 196 ± 17.6) as did FoxP3+ cells (pre = 44, post = 64 cells/?l). Increases in Tregs and FoxP3+ Tregs occurred to the same extent in both groups of adolescent swimmers. This is the first study to show the effect of intense exercise on circulating Treg cells in highly-trained adolescents. The absolute numbers, but not percentage of this specialized set of T Helper lymphocytes increased suggesting that the mechanisms responsible for releasing Tregs into the circulation were distinct from the overall lymphocyte response to exercise. We could not identify specific patterns relating the changes in Tregs to a clinical history of allergy within this population. The acute response to exercise from this field study supports our previous comparisons of exercise-induced lymphocytosis associated with a brief bout of highintensity cycle ergometry exercise in nonathletic asthmatic and healthy children (22). In both studies, we found generally similar patterns of lymphocytosis following exercise for asthmatics and control. In our previous study, CD4+ lymphocyte levels did not differ between asthmatics and controls either at baseline or after exercise. The role of circulating Tregs in mitigating allergy remains enigmatic, requiring further study.